Rhizopine biosensors for plant-dependent control of bacterial gene expression - Haskett, TL; Geddes, BA; Paramasivan, P; Green, P; Chitnavis, S; Mendes, MD; Jorrín, B; Knights, HE; Bastholme, TR; Ramsay, JP; Oldroyd, GED; Poole, PS (Wiley, 2022)
Engineering signalling between plants and microbes could be exploited to establish host-specificity between plant-growth-promoting bacteria and target crops in the environment. We previously engineered rhizopine-signalling circuitry facilitating exclusive signalling between rhizopine-producing (RhiP) plants and model bacterial strains. Here, we conduct an in-depth analysis of rhizopine-inducible expression in bacteria. We characterize two rhizopine-inducible promoters and explore the bacterial host-range of rhizopine biosensor plasmids. By tuning the expression of rhizopine uptake genes, we also construct a new biosensor plasmid pSIR05 that has minimal impact on host cell growth in vitro and exhibits markedly improved stability of expression in situ on RhiP barley roots compared to the previously described biosensor plasmid pSIR02. We demonstrate that a sub-population of Azorhizobium caulinodans cells carrying pSIR05 can sense rhizopine and activate gene expression when colonizing RhiP barley roots. However, these bacteria were mildly defective for colonization of RhiP barley roots compared to the wild-type parent strain. This work provides advancement towards establishing more robust plant-dependent control of bacterial gene expression and highlights the key challenges remaining to achieve this goal.